An Yttrium Hydride–Silane Complex as a Structural Model for a σ‐Bond Metathesis Transition State1. Issue 15 (7th March 2013) - Zhou, Jiliang; Chu, Jiaxiang; Zhang, Yanyan; Yang, Guang; Leng, Xuebing; Chen, Yaofeng
<x xml:space="preserve">Abstract</x> A structural model for the transition state of the σ‐bond metathesis between SiH and ME bonds (M: d0 transition metal) was obtained through the formation of an yttrium hydride–silane complex (see picture). The silane moiety can be either retained or released during the reactions of the complex with other substrates.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>